2014
DOI: 10.1111/micc.12139
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Skeletal Muscle Variations in Microvascular Pressure and Unstressed Blood Volume at the Bedside

Abstract: The new NIRS variables we report could be a practical bench-to-bedside tool to assess venous driving pressure for systemic perfusion and measure changes in Vu within the microvascular bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…[26][27][28] Using NIRS, changes in the MBV were measured during cumulative 45-second-to-1-minute steps of Pcuff, increasing from 5 mmHg to 10, 15, 20, 30, 40, and 50 mmHg. 17 Previous studies have demonstrated a close correlation between Pcuff and pressure in veins. 29 The authors of the study presented here limited Pcuff to a value 10 mmHg lower than the individual patient's diastolic pressure, thus affecting veins rather than arteries.…”
Section: Nirs and Calculation Of Variablesmentioning
confidence: 94%
See 4 more Smart Citations
“…[26][27][28] Using NIRS, changes in the MBV were measured during cumulative 45-second-to-1-minute steps of Pcuff, increasing from 5 mmHg to 10, 15, 20, 30, 40, and 50 mmHg. 17 Previous studies have demonstrated a close correlation between Pcuff and pressure in veins. 29 The authors of the study presented here limited Pcuff to a value 10 mmHg lower than the individual patient's diastolic pressure, thus affecting veins rather than arteries.…”
Section: Nirs and Calculation Of Variablesmentioning
confidence: 94%
“…When examining the microvascular bed, the authors focused mainly on the total Hb tissue concentration contained in venules, small veins, and, to a lesser extent, capillaries, because the Hb contained in the arterial vessels accounts for only 3% of the whole Hb measured with NIRS. 23 The MBV (in milliliters per 100 mL of tissue) was derived from the Hb concentration (g/dL) 17 in blood samples drawn from each patient, taking into account that Hb molecular weight equals 64,500 Da. Because tissue Mb at rest is almost fully oxygenated, 24 it is widely accepted that light absorption measured using NIRS is derived from [HHb] and from oxygenated Hb and Mb.…”
Section: Nirs and Calculation Of Variablesmentioning
confidence: 99%
See 3 more Smart Citations